Where Motley is Worn : Transnational Irish Literatures - Casey, Moira E.; Tucker, Amanda (Lecturer in English) (Book collections on Project MUSE., 2014)
From Ireland's emergence in the global economy and accompanying inward migration to its increasing emigration and racial strife following the 2008 recession, transnationalism has been a meaningful topic in contemporary Irish culture. Most scholars view the "new" multicultural Ireland as a rupture from earlier historical periods. This collection takes a different approach. Using transnationalism as a framework, the volume investigates how the multiple connections that Ireland has fostered with diverse parts of the globe influenced its literary output and production. Where Motley is Worn opens the borders of Irish literary studies, which has traditionally been dominated by a nation-centered focus. The essays in this collection cover both a wide historical period, covering the nineteenth through the twenty-first centuries and a broad geographical range, from Asia to the Caribbean and Latin America. By examining writing that places Irish identity in dialogue with other cultural, national, or ethnic affiliations, the collection allows us to see how Irish literatures have participated in and shaped dynamic cultural flows across the globe.